2013
DOI: 10.1002/bio.2524
|View full text |Cite
|
Sign up to set email alerts
|

Different spectroscopic and molecular modeling studies on the interaction between cyanidin‐3‐O‐glucoside and bovine serum albumin

Abstract: Anthocyanin is one of the flavonoid phytopigments that shows strong antioxidant activity. The cyanidin-3-O-glucoside (C3G) is one of the principal types of anthocyanins. To understand the interaction between C3G and bovine serum albumin (BSA), fluorescence spectroscopy, ultraviolet-visible absorption, Fourier transform infrared spectroscopy, circular dichroism and molecular modeling techniques were used. Binding constant (K(a)) and the number of binding sites (n) were calculated. The quenching mechanism of flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Tang et al . and Cahyana et al . also found that anthocyanins could quench the fluorescence intensity of BSA.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Tang et al . and Cahyana et al . also found that anthocyanins could quench the fluorescence intensity of BSA.…”
Section: Resultsmentioning
confidence: 88%
“… studied the interaction of delphinidin and HSA with multi‐spectral and Tang et al . researched the combination of cyanidin‐3‐ O ‐glucoside and BSA with different spectroscopic and molecular modeling techniques. Cahyana et al .…”
Section: Introductionmentioning
confidence: 99%
“…The docking results demonstrate that the binding of C3G to bovine serum albumin was predominantly due to hydrogen bond interactions and hydrophobic and electrostatic forces. The secondary structure of the protein changed in the presence of C3G (Tang and others ).…”
Section: Food Compounds and Their Capacity To Stabilize Natural Pigmentsmentioning
confidence: 99%
“…BSA, bovine serum albumin; C3G, cyanidin‐3‐O‐glucoside.The binding of C3G to BSA is predominantly due to hydrogen bond interaction, and hydrophobic electrostatic forces. The secondary structure of protein changed in the presence of C3G (Tang and others ). Reproduced with permission granted by John Wiley and Sons, August 1, 2016.…”
Section: Food Compounds and Their Capacity To Stabilize Natural Pigmentsmentioning
confidence: 99%
“…To date, a lot of research has focused on interactions between anthocyanins and serum albumin . However, the interaction between P3G and BSA has not been discussed.…”
Section: Introductionmentioning
confidence: 99%